A method of evaluating the localized corrosion of stainless steels by the condensate of exhaust gases. (4th August 2014) - Sato, E.; Ito, S.; Matsuhashi, R.; Abo, H.
Corrosion of ferritic stainless steels by the condensate of exhaust gases takes the form mainly of localized corrosion, such as pitting or crevices. The localized corrosion of these stainless steels was evaluated using a simulated condensate. The usefulness of the method is assessed and a new index presented for the design of alloys, which takes account of environmental conditions.